Comparative Research Approaches - Ostry, Sylvia (Relations industrielles / Industrial Relations, 1966)
In the minds of many people, the Dominion Bureau of Statistics appears as a kind of factory producing data. It is more than that. This paper shows that the Bureau is taking new leads in the field of developmental and analytical research bearing on revised and new statistical series.